The elasmobranch Cretolamna appendiculata in the Upper Cretaceous - Gosau beds near Stranice, Eastern Slovenia - Mikuž, Vasja (Geologija, 2003)
A tooth of chodrostean fish, found in Upper Cretaceous Gosau facies in the quarry near Stranice, is described. In the rocks occurs an abundance of various fossil remains, from the predominanting avertebrates to rare vertebrates. Morphology and size of tooth indicate it belong to the very frequent Cretaceous - Paleogene species Cretolamna appendiculata (Agassiz, 1843).